ANALISIS PENGALAMAN, SKEPTISISME PROFESIONAL AUDITOR TERHADAP KEMAMPUAN MENDETEKSI FRAUD (Study Kasus Badan Pemeriksa Keuangan Perwakilan Provinsi Bengkulu) - Rina Trisna Yanti; Herlin Herlin (Jurnal Ilmu Akuntansi, 2019)
The purpose of this study to analyze the relationship of experience and skepticism of auditor professionals with the ability to detect fraud (fraud) in Supreme Audit Agency, Representative of Bengkulu Province.This research includes descriptive research which is a problem formulation concerning the question of the existence of independent variables, either on one or more variables. Research respondents are auditors who work in Supreme Audit Agency, Representative of Bengkulu Province which amounted to 37 people. Data collection using questionnaire and data analysis using sperman rank correlation. The results showed that there is a significant relationship between the auditor's experience with the auditor's ability to detect fraud at Supreme Audit Agency, Representative of Bengkulu Province (t count 29,644> t table 1,690). That is, the more experienced an auditor the ability to detect higher fraud. The correlation of the auditor's experience with the auditor's ability to detect fraud of .834 is at a very strong level of relationship. There is a significant correlation between professional skepticism of auditor with auditor ability to detect fraud at Supreme Audit Agency, Representative of Bengkulu Province(t count 86,335> t table 1,690) That is, the higher skepticism of professional auditor hence ability to detect fraud also higher.Correlation of skepticism of professional auditor with auditor ability to detect fraud of 0.936 is at a very strong level of relationship